1992
DOI: 10.1126/science.1532458
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Human Cyclin A and Adenovirus E1A-Associated p107 Protein

Abstract: The products of the adenovirus early region 1A (E1A) gene are potent oncoproteins when tested in standard transformation and immortalization assays. Many of the changes induced by E1A may be due to its interaction with cellular proteins. Four of these cellular proteins are the retinoblastoma protein (pRB), p107, cyclin A, and p33cdk2. The pRB and p107 proteins are structurally related and have several characteristics in common, including that they both bind to the SV40 large T oncoprotein as well as to E1A. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
114
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(118 citation statements)
references
References 23 publications
3
114
0
1
Order By: Relevance
“…Studies on some of the above mentioned proteins have indicated that the residues homologous to the p130 cyclin binding region are directly involved in cyclin/cdk interactions. p107 has been shown to interact with both cyclins A and E and several studies have suggested that the region homologous to the p130 cyclin binding region is critical for these interactions Faha et al, 1992;Zhu et al, 1995a, b). A region similar to the p130 cyclin binding region is found at the amino-termini of p21 cip1 , p27 kip1 and p57 kip2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on some of the above mentioned proteins have indicated that the residues homologous to the p130 cyclin binding region are directly involved in cyclin/cdk interactions. p107 has been shown to interact with both cyclins A and E and several studies have suggested that the region homologous to the p130 cyclin binding region is critical for these interactions Faha et al, 1992;Zhu et al, 1995a, b). A region similar to the p130 cyclin binding region is found at the amino-termini of p21 cip1 , p27 kip1 and p57 kip2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the interactions with the D cyclins, p107 and p130 stably interact with cyclin A/cdk2 and cyclin E/cdk2 complexes in vivo and in vitro Faha et al, 1992Faha et al, , 1993Lees et al, 1992;Hannon et al, 1993;Li et al, 1993;Peeper et al, 1993). This property is not held in common with pRB and the signi®cance of this di erence remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human cyclin A was initially identified as the p60 protein associated with the adenovirus ElA oncoprotein (Harlow et al, 1986;Giordano et al, 1989;Pines and Hunter, 1990). The association between cyclin A and ElA was later shown to be mediated by pRblO7, a homologue of the retinoblastoma susceptibility gene product pRblO5 (Ewen et al, 1991Faha et al, 1992). The cyclin A/pRblO7 complex was also found to contain CDK2 and E2F (Mudryj et al, 1991;Cao et al, 1992;Devoto et al, 1992;Pagano et al, 1992a;Shirodkar et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Among the pRB family proteins, p107 and p130 are structurally closer to each other than to pRB and share unique properties allowing interaction with cyclins and Cdks Faha et al, 1992;Lees et al, 1992;Cobrinik et al, 1993;Zhu et al, 1995;Smith and Nevins, 1995). Through this interaction, p107 and p130 are capable of inhibiting the kinase activity of cyclin ± Cdk complexes (Zhu et al, 1995;Woo et al, 1997;Castano et al, 1998).…”
Section: Introductionmentioning
confidence: 99%